Witnessing Torture Perspectives of Torture Survivors and Human Rights Workers (Palgrave Studies in Life Writing, 2018)
This book demonstrates a new, interdisciplinary approach to life writing about torture that situates torture firmly within its socio-political context, as opposed to extending the long line of representations written in the idiom of the proverbial dark chamber. By dismantling the rhetorical divide that typically separates survivors' suffering from human rights workers' expertise, contributors engage with the personal, professional, and institutional dimensions of torture and redress. Essays in this volume consider torture from diverse locations - the Philippines, Argentina, Sudan, and Guantánamo, among others. From across the globe, contributors witness both individual pain and institutional complicity; the challenges of building communities of healing across linguistic and national divides; and the role of the law, art, writing, and teaching in representing and responding to torture.